PENGARUH PEMBINAAN, DISIPLIN DAN MOTIVASI TERHADAP KINERJA GURU PAUD KEC. TALANG KELAPA - Andriani, Dessi (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
This study aims to determine the influence between Development and Discipline either partially or simultaneously on the performance of Teachers In PAUD-PAUD in Kec. Talang Kelapa. Hypotheses submitted (1). Suspected Coaching Positively and significantly affect the performance of teachers in early childhood in the district. Talang Kelapa (2) .Dispossible Displin positively and significantly influence on PAUD Teacher Performance in Kec. Talang Kelapa. (3) Positive and Real Motivation affect the performance of PAUD teachers in Kec. Talang Kelapa. (4). Alleged Fostering Discipline and motivation jointly affect the performance of Teachers In PAUD in Kec. Talang Kelapa which amounted to 50 people, with the research sample taken all by using census technique. Instruments Data collection used is a questionnaire that uses Likert scale which is compiled based on the summarizes of the various theories embodied into operational variables, while testing on the research instrument is done through validity and reliability test. Data analysis was performed through a requirement test consisting of normality test using Smirnov kolmogrof test, homogeneity test using Chi square test, and linearity test using One-Way Anova. Hypothesis testing dilakuka by using regression analysis and correlation between the guidance and displin variable as a free variable on the performance of teachers as a dependent variable. The T-test is used to determine the effect of the three independent variables of Discipline Development and Motivation parcially on teacher performance as dependent variable. While the F-Test to determine the effect of the three independent variables Development of Displin and Motivation simultaneously on the performance of teachers as a dependent variable. Signature level used in this research is α = 5%. The results showed that (1). Positive and tangible coaching influences Teacher Performance in PAUD in Kec. Talang Kelapa. (2) Displin positively and significantly influence on Teacher Performance in PAUD in Kec. Talang Kelapa. (3) Motivation positively and significantly influence on PAUD Teacher Performance in Kec. Talang Kelapa. (4) Development of Discipline and Motivation together influential on Teacher Performance In PAUD in KEC. Talang Kelapa.Key Words: Performance of early childhood teachers, coaching, discipline, motivation, Talang Kelapa sub-distric